An isotopic study on oxygen uptake/exchange over ceria-praseodymia mixed oxides with pulse experiments using 18O2: Implications on soot combustion activities in the GDI (Gasoline Direct Injection) context - Martínez-Munuera, Juan Carlos; Cortés-Reyes, Marina; García-García, Avelina (Elsevier, 2023)
This research work focuses on a preliminary study of the behaviour of several ceria-praseodymia mixed oxides along with three model catalysts under isotopic oxygen pulses at different temperatures in an attempt to investigate their ability to interact with 18O2 (uptaking/releasing/exchanging) with their own lattice oxygen, under conditions which could simulate those existing in GDI exhaust gases. Furthermore, these ceria-praseodymia mixed oxides were studied to explore their responses towards soot combustion under two consecutive 18O2 pulses at 500 °C. It was observed that the capacity of oxygen activation and uptake is very dependent on the nature of the catalyst. Ce1−xPrxO2-δ catalysts present different responses in the O2 activation and uptake processes, as a function of temperature, praseodymium content and method of preparation. Moreover, some of these ceria-praseodymia formulations exhibited high soot combustion activity with a marked intervention of unlabelled active oxygen species during the inert period after the 18O2 pulse.
Keywords: Gasolina; Catalizadores; Eliminación de contaminantes; Catálisis; Vehículos